Targeting cellular source-specific CXCL9 signaling for immunotherapy in oral squamous cell carcinoma - Qiu, Miao; Wang, Ling; Tang, Honglin; Jiang, Shan (Frontiers in Immunology, 2026)
Oral squamous cell carcinoma (OSCC) remains a clinical challenge due to its high recurrence, metastatic potential, and limited responsiveness to current immunotherapies. Within the tumor microenvironment (TME), the C-X-C motif chemokine ligand 9 (CXCL9) plays a pivotal yet paradoxical role, functioning as both an anti-tumor effector and a tumor-promoting factor depending on its cellular origin. This review proposes that the function of CXCL9 is not intrinsic but dictated by the interplay among its cellular source, microenvironmental context, and receptor-expressing cells. We delineate how this tripartite crosstalk influences immune checkpoint blockade (ICB) outcomes through mechanisms such as T-cell suppression, regulatory T cells recruitment, and PD-L1 upregulation. Myeloid cell-derived CXCL9 generally mediates anti-tumor immunity by recruiting cytotoxic lymphocytes, whereas CXCL9 produced by stromal cells like cancer-associated fibroblasts often contributes to metastasis and immune evasion. Given this complexity and unique immunosuppressive and fibrotic properties of OSCC, we argue that simply augmenting or blocking CXCL9 is insufficient. Instead, overcoming ICB resistance in OSCC requires a precision strategy focused on targeting cell-specific CXCL9 signaling. Ultimately, dissecting and therapeutically navigating the source-specific CXCL9 network is essential to transform the OSCC TME and improve clinical outcomes.